Association between indoor residual spraying and pregnancy outcomes: a quasi-experimental study from Uganda. (18th March 2022) - Roh, Michelle E; Mpimbaza, Arthur; Oundo, Brenda; Irish, Amanda; Murphy, Maxwell; Wu, Sean L; White, Justin S; Shiboski, Stephen; Glymour, M Maria; Gosling, Roly; Dorsey, Grant; Sturrock, Hugh
Abstract: Background: Malaria is a risk factor for adverse pregnancy outcomes. Indoor residual spraying with insecticide (IRS) reduces malaria infections, yet the effects of IRS on pregnancy outcomes are not well established. We evaluated the impact of a large-scale IRS campaign on pregnancy outcomes in Eastern Uganda. Methods: Birth records ( n  = 59 992) were obtained from routine surveillance data at 25 health facilities from five districts that were part of the IRS campaign and six neighbouring control districts ∼27 months before and ∼24 months after the start of the campaign (January 2013-May 2017). Campaign effects on low birthweight (LBW) and stillbirth incidence were estimated using the matrix completion method (MC-NNM), a machine-learning approach to estimating potential outcomes, and compared with the difference-in-differences (DiD) estimator. Subgroup analyses were conducted by HIV and gravidity. Results: MC-NNM estimates indicated that the campaign was associated with a 33% reduction in LBW incidence: incidence rate ratio (IRR) = 0.67 [95% confidence interval (CI): 0.49–0.93)]. DiD estimates were similar to MC-NNM [IRR = 0.69 (0.47–1.01)], despite a parallel trends violation during the pre-IRS period. The campaign was not associated with substantial reductions in stillbirth incidence [IRRMC-NNM  = 0.94 (0.50–1.77)]. HIV status modified the effects of the IRS campaign on LBW [βIRSxHIV  = 0.42 (0.05–0.78)], whereby HIV-negative women appeared to benefit from the campaign [IRR = 0.70 (0.61–0.81)], but not HIV-positive women [IRR = 1.12 (0.59–2.12)]. Conclusions: Our results support the effectiveness of the campaign in Eastern Uganda based on its benefit to LBW prevention, though HIV-positive women may require additional interventions. The IRS campaign was not associated with a substantively lower stillbirth incidence, warranting further research.